Microfluidic Synthesis of Actuating Microparticles from a Thiol-Ene Based Main-Chain Liquid Crystalline Elastomer - Hessberger, Tristan (Polymers (Basel), 2016)
In this article the microfluidic synthesis of strongly actuating particles on the basis of a liquid crystalline main-chain elastomer is presented. The synthesis is carried out in a capillary-based co-flow microreactor by photo-initiated thiol-ene click chemistry of a liquid crystalline monomer mixture. These microparticles exhibit a deformation from a spherical to a rod-like shape during the thermal-initiated phase transition of the liquid crystalline elastomer (LCE) at which the particles’ aspect ratio is almost doubled. Repeated contraction cycles confirm the complete reversibility of the particles’ actuation properties. The transition temperature of the LCE, the temperature range of the actuation process as well as the magnitude of the particles’ aspect ratio change are studied and controlled by the systematic variation of the liquid crystalline crosslinker content in the monomer mixture. Especially the variable actuation properties of these stimuli-responsive microparticles enable the possibility of an application as soft actuators or sensors.